Alterations in the oral microbiome in HIV-infected participants after antiretroviral therapy administration are influenced by immune status. (19th June 2018) - Presti, Rachel M.; Handley, Scott A.; Droit, Lindsay; Ghannoum, Mahmoud; Jacobson, Mark; Shiboski, Caroline H.; Webster-Cyriaque, Jennifer; Brown, Todd; Yin, Michael T.; Overton, Edgar T.
Abstract : Objective: To characterize the oral bacterial microbiome in HIV-infected participants at baseline and after 24 weeks of EFV/FTC/TDF. Design: Thirty-five participants co-enrolled in two AIDS Clinical Trials Group (ACTG) studies, A5272 and A5280, with paired saliva samples and complete data sets were assessed. Methods: Paired saliva samples were evaluated for bacterial microbiome using 16S rDNA PCR followed by Illumina sequencing. Diversity and differential abundance was compared between groups. A random forest classification scheme was used to determine the contribution of parameters in classifying participants' CD4 + T-cell count. Results: Bacterial communities demonstrated considerable variability both within participants and between timepoints, although they became more similar after 24 weeks of ART. At baseline, both the number of taxa detected and the average alpha diversity were variable between participants, but did not differ significantly based on CD4 + cell count, viral load or other factors. After 24 weeks of ART samples obtained from participants with persistently low CD4 + T-cell counts had significantly higher bacterial richness and diversity. Several differentially abundant taxa, including Porphyromonas species associated with periodontal disease, were identified, which discriminated between baseline and posttreatment samples. Analysis demonstrated that although inflammatory markers are important in untreated disease, the salivary microbiome may play an important role in CD4 + T-cell count recovery after ART. Conclusion: Shifts in the oral microbiome after ART initiation are complex, and may play an important role in immune function and inflammatory disease. Abstract : Supplemental Digital Content is available in the text